FEATURES OF EMOTIONAL BURNOUT AND ITS ROLE IN THE STRUCTURE OF MALADAPTATION OF VOLUNTEERS, WHOSE ACTIVITIES ARE RELATED TO THE PROVISION OF MILITARY PERSONNEL IN THE ATO ZONE - Markova, Marianna; Glagolych, Slava (PSYCHOLOGICAL JOURNAL, 2018)
In the article, the features of emotional burnout and psychological maladaptation of volunteers are analyzed. The purpose of the work was to study the features of emotional burnout and psychological maladaptation of Ukrainian volunteers. Using the questionnaire “Assessment of professional maladaptation” by O. N. Rodina in the version of M. A. Dmytrieva and the methodology “Diagnostics of the level of “emotional burnout” by V. V. Boyko, it was examined 147 volunteers, whose activities were related to the provision of military personnel in the ATO zone for at least 1 year. It is established that 29.3% of volunteers have phenomena or signs of maladaptation, while in 61.2%, there are certain phases of the emotional burnout syndrome (34.0% − those that are being formed, 27.2% − formed). In volunteers with signs of maladaptation, it was revealed significant symptoms of emotional burnout in almost all factors and symptoms. At the same time, the indicators of the experience of psycho-traumatic circumstances, the feeling of “being trapped in a cage”, anxiety and depression, expansion of the sphere of saving of emotions, depersonalization, psychosomatic and psycho-vegetative disorders correspond to the formed symptoms; and indicators of dissatisfaction with oneself, inadequate emotional selective response, reduction of professional duties, emotional detachment and emotional deficiency correspond to the level the symptom that is being formed. The differentiation of the examined people into groups depending on the intensity of the emotional burnout syndrome and the level of maladaptation allowed to establish that in the volunteers with the low level of maladaptation and the symptoms of the emotional burnout, which was being formed, the burnout was in the phase of “Resistibility” with the dominance of the symptoms of the expansion of the sphere of emotional saving. In the volunteers with existing disorders of maladaptation and emotional burnout, which was being formed, this formation took place in the phase “Intenseness”, and in the volunteers with existing maladaptation phenomena and the formed phases of burnout, it was mainly in the phase of “Intenseness” with high rates for all phases. This is established that the structure of maladaptive manifestations with an increase in the phenomena of emotional burnout has been changed: in the initial phases, phenomena of emotional disorders, social dysfunction and asthenia dominated, with time the phenomena of insomnia with diminished motivation, which in the terminal phases were accompanied by a decrease in activity, dominated. The obtained data allow us to conclude that there are signs of emotional burnout and psychological maladaptation, as well as their mutual connection in people whose activities are connected with volunteering.